«Shanghai» in the Сentre of Irkutsk. Chinese Market Ecology - ДятловВиктор Иннокентьевич; КузнецовРоман Эдуардович (Journal of Economic Sociology, 2010)
The Chinese market appeared at the end of 1990s in Irkutsk entered the consciousness of the urban community as Shanghai. Maybe this word unites the past experience of all the meanings of “Chinese”, “slums”, “crowd”. The market became more than just a usual place for trade. China has entered through this Shanghai market, now this is the place for meeting of two civilizations and cultures. This is the headache for the city authorities and their tough issue to tackle. Irkutsk mass media pays constant non-kind attention to the Shanghai market. This is the object of the criticism of “Chinese expansion” and “yellow danger” for many local policy makers. This paper considers Shanghai market both from inside point of view as social organism and outside point of view with regard to the city’s society.